ASPECTOS DE LA BIOLOGIA DE RHAGOLETIS TOMATIS FOOTE (DIPTERA: TEPHRITIDAE) EN POBLACIONES DE LA II REGION DE CHILE - Frías L., Daniel; Northland L., Irma; Capetillo A., Juana (Acta Entomológica Chilena, 2022)
Observations both at the laboratory and in the field prove that probably Rhagoletis tomatis has at least five to six generations per year. This species present a low pupal diapause. Females deposite their eggs gregariously in unripen fruits. After ovipositing the females dragg the ovipositor in circle near of puncture and probably deposit a pheromone that is atractive for other females.